1999
DOI: 10.1007/bf02449932
|View full text |Cite
|
Sign up to set email alerts
|

Lake Shira, a Siberian salt lake: ecosystem structure and function

Abstract: Abstract. The specific composition, vertical distribution and daily migration of plankton in a meromictic salt lake, Lake Shira, have been investigated. The main structural components of the ecosystem are bacteria, algae and crustaceans. Since the late 1970s, blue-green algae are reported as dominant. Nowadays the phytoplankton is dominated by Lyngbya contorta, Microcystis ichtyoblabe (Cyanophyta), Cyclotella tuberculata (Bacillariophyta) and Dictyosphaerium tetrachotomum (Chlorophyta). The zooplankton of Lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 3 publications
(5 reference statements)
4
19
0
Order By: Relevance
“…Studies of pelagic communities in lakes are often focused on the vertical structure of the plankton, the vertical distribution of which reflects physiological, behavioral and ecological preferences of organisms. Lake Shira and Lake Shunet (Khakassia, Russia) are meromictic lakes (Zotina et al 1999;Rogozin et al 2009), where Gammarus is one of the few dominant species among zooplankton. Yemelyanova et al (2002) have been shown that in Lake Shira the highest densities of Gammarus occur in sublittoral area.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of pelagic communities in lakes are often focused on the vertical structure of the plankton, the vertical distribution of which reflects physiological, behavioral and ecological preferences of organisms. Lake Shira and Lake Shunet (Khakassia, Russia) are meromictic lakes (Zotina et al 1999;Rogozin et al 2009), where Gammarus is one of the few dominant species among zooplankton. Yemelyanova et al (2002) have been shown that in Lake Shira the highest densities of Gammarus occur in sublittoral area.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the reservoir and its ecosystem can be found in the work of Zotina et al (1999), Gaevsky et al (2002), Kalacheva et al (2002), Kopylov et al (2002b), Rogozin et al (2009).…”
Section: Description Of Shira Lakementioning
confidence: 99%
“…The use of this reservoir as the popular recreation place and its balneological properties put special constraints on its water quality. During recent years, several studies on the structure and functioning of Lake Shira were performed (Zotina et al 1999;Gaevsky et al 2002;Kalacheva et al 2002;Kopylov et al 2002b) and a first mathematical model of the lake's ecosystem was created .…”
Section: Introductionmentioning
confidence: 99%
“…During the summer period Lake Shira is a stratified water body with heterogeneous distribution of zooplankton (Zotina et al 1999). Calanoid copepods Arctodiaptomus salinus and rotifers Brachionus plicatilis are the dominant species accounting for 95% of the total zooplankton biomass (Zotina et al 1999). The representative of bentho-plankton is the amphipod Gammarus lacustris (Yemelyanova et al 2002).…”
Section: Methodsmentioning
confidence: 99%